Role of Internet of Things (IoT) in Retail Business and Enabling Smart Retailing Experiences - Hossain, Md. Shakawat; Chisty, Nur Mohammad Ali; Hargrove, Donyea Lamont; Amin, Ruhul (Asian Business Review, 2021)
Internet of Things (IoT) is anticipated to be one of the primary megatrends up in innovation. Integrated with the current and upcoming mobility of digital gadgets, it offers ground to applications in numerous domains, including retail. The capability of sensors for setting applicable, customized, real-time, and intuitive communication with buyers and customers is considered to be a driving force of traffic and exchange, a facilitator of development along the way to elevate their purchasing experience. Simultaneously, IoT can serve to further develop relationships and foundations for more viable retail business and digital store management. Currently, digitally savvy customers expect an Omnichannel experience at each touchpoint. They need to track down the ideal data at the perfect time at the right location. Location-based innovation in a retail setting identifies the way that users take to arrive at specific areas of a retail store and helps upgrade the shopping experience. This is the reason the Internet of Things (IoT) is beginning to take the online business to a higher level, and will probably disrupt the conventional retail processes on a significant scale in the coming time. This paper surveys and arranges the most common applications of IoT and solutions for successful marketing at retail from the point of retailers and customers as well as from the point of manufacturers confronting framework or communication-related issues. We propose a model that demonstrates the potential that IoT has as compared to standard industry practices of retail to drive business results and gain an upper hand. In this paper, we’ve likewise talked about the new developments and new techniques for the organizations to accomplish competitive advantage brought about by the uses cases of IoT, particularly in the field of mobile sensors. Such developments are likely the most prominent factor in the coming years to make progress in the advanced economy.